Pathway and policy analysis to China's deep decarbonization. Issue 1 (2nd January 2017) - Liu, Qiang; Chen, Yi; Teng, Fei; Tian, Chuan; Zheng, Xiaoqi; Zhao, Xuchen
ABSTRACT: The Paris Agreement marks the beginning of a new era in the global response to climate change, which further clarifies the long-term goal and underlines the urgency addressing climate change. For China, promoting the decoupling between economic growth and carbon emissions as soon as possible is not only the core task of achieving the medium- and long-term goals and strategies to address climate change, but also the inevitable requirement for ensuring the sustainable development of economy and society. Based on the analysis of the historical trends of the economy and social development, as well as society, energy consumption, and key end-use sectors in China, this paper studies the deep carbon emission reduction potential of carbon emission of in energy, industry, building, and transportation and other sectors with "bottom-up" modeling analysis and proposes a medium- and long-term deep decarbonization pathway based on key technologies' mitigation potentials for China. It is found that under deep decarbonization pathway, China will successfully realize the goals set in China's Intended Nationally Determined Contributions of achieving carbon emissions peak around 2030 and lowering carbon dioxide emissions per unit of gross domestic product (GDP) by 60–65% from the 2005 level. From 2030 onward, the development of nonfossil energy will further accelerates, and the share of nonfossil energies in primary energy will amounts to about 44% by 2050. Combined with the acceleration of low-carbon transformation in end-use sectors including industry, building, and transportation, the carbon dioxide emissions in 2050 will fall to the level before 2005, and the carbon dioxide emissions per unit of GDP will decreases by more than 90% from the 2005 level. To ensure the realization of the deep decarbonization pathway, this paper puts forward policy recommendations from four perspectives, including intensifying the total carbon dioxide emissions cap and strengthening the related institutional systems and regulations, improving the incentive policies for industrial low-carbon development, enhancing the role of the market mechanism, and advocating low-carbon life and consumption patterns.